ANALISIS YURIDIS HADHANAH AYAH MENURUT HUKUM KELUARGA ISLAM (STUDI KASUS PUTUSAN PENGADILAN AGAMA MOJOKERTO NOMOR 833/ Pdt.G/ 2021/ PA. Mr). - Sherien Defrinanda; Setyaningsih (Faculty of Law, Universitas Trisakti, 2023)
For minor children, the mother is legally entitled to custody. The author focuses on the conditions for a father to be entitled to Hadhanah privileges. The formulation of the problem in this research is whether a father is entitled to hadhanah if the father prevents a child who is not yet mumayyiz from his biological mother according to Indonesian Islamic Family Law and whether the decision of the religious court number 833/Pdt.G/2021/PA. Mr. is in accordance with Islamic family law. The research method was carried out using a normative juridical type with a descriptive analytical approach. Primary, secondary and tertiary legal sources were questioned to obtain secondary data. Qualitative investigation and the application of deductive reasoning are components of the literature analysis process. Based on the results of research and discussion, children under the age of 12 have the right to their mother in accordance with the Hadhanah rules as outlined in Article 105 of the Compilation of Islamic Law (KHI). The child must be raised by the mother because the mother is not crazy and is capable and does not behave badly. In conclusion, the judge actually gave Hadhanah rights to the father rather than the mother.